2020
DOI: 10.1177/0306624x20978204
|View full text |Cite
|
Sign up to set email alerts
|

Does Reassessment Improve Prediction? A Prospective Study of the Sexual Offender Treatment Intervention and Progress Scale (SOTIPS)

Abstract: This prospective study examined the predictive validity of the Sex Offender Treatment Intervention and Progress Scale (SOTIPS; McGrath et al., 2012), a sexual recidivism risk/need tool designed to identify dynamic (changeable) risk factors relevant to supervision and treatment. The SOTIPS risk tool was scored by probation officers at two sites ( n = 565) for three time points: near the start of community supervision, at 6 months, and then at 12 months. Given that conventions for analyzing dynamic prediction st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 72 publications
2
19
0
Order By: Relevance
“…Within samples of men convicted of sexually motivated crimes, reassessed proximal scores also predicted recidivism better than prior scores (Babchishin & Hanson, 2020;Hanson et al, 2020). Of specific interest, Babchishin and Hanson (2020) found that prediction results differed based on the type of recidivism.…”
Section: Prospective Prediction In the Communitymentioning
confidence: 94%
“…Within samples of men convicted of sexually motivated crimes, reassessed proximal scores also predicted recidivism better than prior scores (Babchishin & Hanson, 2020;Hanson et al, 2020). Of specific interest, Babchishin and Hanson (2020) found that prediction results differed based on the type of recidivism.…”
Section: Prospective Prediction In the Communitymentioning
confidence: 94%
“…Compared to Time 1 and 2, Time 3 yielded the cleanest correlation matrix, the most consistent number of factors (according to the various factor retention criteria), and the best fit indices. Time 3 scores were also privileged because, as a dynamic risk tool, the most recent scores are expected to be the most valid, and there was some evidence that this was the case in the current sample (Hanson et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…However, recently, researchers have begun exploring various ways to capture fluctuations in dynamic risk over time. Instead of relying on the most recent assessment, other methods (e.g., using a rolling mean, the highest score to date, the lowest score to date, or the moving rolling mean; Babchishin & Hanson, 2020; Chu, Thomas, Daffern, et al, 2013; Davies et al, 2021; Hanson et al, 2021; Howard & Dixon, 2013; Lloyd et al, 2020) have been investigated to account for measurement error associated with a single assessment (Epstein, 1983) and consider whether periods of crisis or improvement, as reflected by changes in the presence of stable and acute dynamic risk factors, are more important than an enduring presentation. Additionally, researchers have begun investigating the dynamic nature of acute risk assessments and their incremental validity compared to an initial assessment (Babchishin & Hanson, 2020; Davies et al, 2021; Hanson et al, 2021; Howard & Dixon, 2013; Lloyd et al, 2020).…”
Section: Risk Assessment In Forensic Mental Health Inpatient Settingsmentioning
confidence: 99%